A Pipeline for Natural Small Molecule Inhibitors of Endoplasmic Reticulum Stress - Correia da Silva, Daniela; Valentão, Patrícia; Andrade, Paula B.; Pereira, David M. (Frontiers in Pharmacology, 2022)
The homeostasis of eukaryotic cells is inseverable of that of the endoplasmic reticulum (ER). The main function of this organelle is the synthesis and folding of a significant portion of cellular proteins, while also being the major calcium reservoir of the cell. Upon unresolved ER stress, a set of stress response signaling pathways that are collectively labeled as the unfolded protein response (UPR) is activated. Prolonged or intense activation of this molecular machinery may be deleterious. It is known that compromised ER homeostasis, and consequent UPR activation, characterize the pathogenesis of neurodegenerative disease. In an effort to discover new small molecules capable of countering ER stress, we subjected a panel of over 100 natural molecules to a battery of assays designed to evaluate several hallmarks of ER stress. The effect of the compounds on calcium homeostasis, key gene and protein expression, and levels of protein aggregation were evaluated in fibroblasts, and subsequently in neuronal cells. This framework resulted in the identification of several bioactive molecules capable of countering ER stress and deleterious events associated to it, among which delphinidin stands out as the most promising candidate against neurodegeneration.